Applications of a high performance platinum nanocatalyst for the oxidation of alcohols in water - Maity, Prasenjit; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Green Chemistry, 2009)
Nanoparticles of platinum (NP-Pt), have been synthesized by supporting high nuclearity anionic carbonyl cluster (Chini cluster) on a water soluble anion exchanger, and the performance of this material, 1, as an oxidation catalyst for alcohols in water has been studied. The E-factor for the synthesis of NP-Pt by this method has been calculated and compared with that of other NP-Pt recently reported in the literature. With 1 as a catalyst, oxidations of a variety of primary and secondary alcohols by dioxygen are achieved and high turnover numbers and selectivities are obtained. The performances of 1 in the oxidation of benzyl alcohol and 1-phenylethanol are compared with those of three other platinum catalysts. These are platinum nanoparticles 2 prepared by the hydrogen reduction of [PtCl6](2-) supported on the same water soluble polymer, 5% Pt on carbon, and 5% Pt on alumina, designated as 3 and 4, respectively. 1 has been found to be considerably more active than 2- 4 and also other reported water soluble platinum nanocatalysts. After many turnovers (similar to 1000 and similar to 165 for benzyl alcohol and 1-phenyl ethanol, respectively) partial deactivation (similar to 40%) is observed, but the deactivated catalyst can be fully regenerated by treatment with dihydrogen. The TEM data of fresh, deactivated and regenerated 1 show a correlation between the particle size and activity. A mechanism consistent with this and other experimental observations including XPS data is proposed.